2021
DOI: 10.1093/intqhc/mzab043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of barcode technology on medication preparation safety: a quasi-experimental study

Abstract: Background Medication errors are a common problem in hospitals and a major driver of adverse patient outcomes. Barcode verification technology is a promising strategy to help ensure safe medication preparation practices. Objectives The objectives of this study were (i) to assess the effects of a barcode-assisted medication preparation and administration system regarding the rate of medication preparation errors and (ii) to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Management of the intra-hospital drug chain is inefficient, with a lack of transparency in some processes and not completely safe in terms of administration to the patient ( Raijada et al, 2021 ). This study has identified and collected the five main problems regarding drug management in hospitals reported in the literature, and that the authors have verified during their real work in hospitals, that is: inadequate presentation format of the data to be recorded ( Küng et al, 2021 ); current procedures must be adapted to regulatory changes; inefficient data capture procedure ( Fan et al, 2022 ); incomplete data recording ( Chien et al, 2021 ); and poor analysis of the results ( Kapetaneas & Kitsios, 2022 ). This is the first novelty of this proposal regarding the state of the art.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of the intra-hospital drug chain is inefficient, with a lack of transparency in some processes and not completely safe in terms of administration to the patient ( Raijada et al, 2021 ). This study has identified and collected the five main problems regarding drug management in hospitals reported in the literature, and that the authors have verified during their real work in hospitals, that is: inadequate presentation format of the data to be recorded ( Küng et al, 2021 ); current procedures must be adapted to regulatory changes; inefficient data capture procedure ( Fan et al, 2022 ); incomplete data recording ( Chien et al, 2021 ); and poor analysis of the results ( Kapetaneas & Kitsios, 2022 ). This is the first novelty of this proposal regarding the state of the art.…”
Section: Discussionmentioning
confidence: 99%
“…Currently the data required according to the regulations are the lot number and the expiration date of the drug, which must appear incorporated in the secondary package (outer package) ( Felix et al, 2019 ). However, this presentation format does not correspond to current needs ( Küng et al, 2021 ; Hsieh et al, 2021 ). This secondary package is discarded by hospital pharmacy services due to lack of identification of the individual doses, and the content is extracted either for processing or for conversion into unit doses.…”
Section: Existing Problems With the Traceability Of Medicines In Hosp...mentioning
confidence: 99%
“…Related articles Barcode Medication Administration -BCMA Refs. (Barakat & Franklin, 2020;Burkoski et al, 2019;Cabilan et al, 2017;González-Bueno et al, 2021;Kennedy & Massey, 2019;Küng et al, 2021;Mulac et al, 2021;Risør et al, 2017;Van Der Veen et al, 2018) Electronic Health System -HER Refs. (Amato et al, 2017;Biltoft & Finneman, 2018;Debono et al, 2017;Griffon et al, 2017;Jurado et al, 2018;Kirkendall et al, 2020;Pontefract et al, 2018;Reinhardt et al, 2019;Shah et al, ).…”
Section: Technologiesmentioning
confidence: 99%
“…In some cases, the use of electronic registration was associated with BCMA technology Refs. (Cabilan et al, 2017;Küng et al, 2021;Mulac et al, 2021;Risør et al, 2017). Health Systems, or Health Information System (HIS), are mentioned in two studies Refs.…”
Section: Technologiesmentioning
confidence: 99%
“…Barcode scanning technology is a component of ‘closed loop’ medication administration and is expected to reduce error rates by between 41% and 56% 1. In the Healthcare Information and Management Systems Society (HIMSS) maturity model, which consists of stages 0 (least mature) to 7 (most mature),2 closed loop medication administration is required to achieve stage 6 or higher.…”
Section: Introductionmentioning
confidence: 99%